The effect of changes in the bulk dielectric constant on the DNA torsional properties - Souza, Fátima Pereira de; Agostinho Neto, Augusto; Fossey, Marcelo Andrés [UNESP]; Ruggiero Neto, Joao (Wiley-Blackwell, 2007)
The effect of changes in the bulk dielectric constant on the DNA torsional properties was evaluated from plasmid circularization reactions. In these reactions, pUC18 previously linearized by EcoRI digestion was recircularized with T4 DNA ligase. The bulk dielectric constant of the reaction medium was decreased by the addition of different concentrations of neutral solutes: ethylene glycol, glycerol, sorbitol, and sucrose, or increased by the addition of glycine. The topoisomers generated by the ligase reaction were resolved by agarose-gel electrophoresis. The DNA twist energy parameter (K), which is an apparent torsional constant, was determined by linearization of the Gaussian topoisomers' distribution. It was observed that the twist energy parameter for the given solutes is almost linearly dependent on the bulk dielectric constant. In the reaction buffer, the twist energy parameter was determined to be 1100 +/- 100. By decreasing the dielectric constant to 74 with the addition of sorbitol, the value of the parameter reaches K = 900 +/- 100, whereas the addition of ethylene glycol leads to kappa = 400 +/- 50. Upon addition of glycine, which resulted in a dielectric constant equal to 91, the value of the twist energy parameter increased to K 1750 +/- 100. (c) 2007 Wiley Periodicals.
Keywords: DNA; dielectric constant; electrophoresis; torsional energetic parameter; helical twist angle; neutral solutes